Upaya Pemerintah Desa Mendorong Partisipasi Masyarakat Dalam Pembangunan Desa Oluhuta Kecamatan Atinggola Kabupaten Gorontalo Utara - Riyanti Samaun; Bala Bakri; Achmad Risa Mediansyah (Fakultas Ilmu Sosial dan Ilmu Poliitik Universitas Ichsan Gorontalo, 2022)
This study aims to find out the village government efforts to encourage community participation in the development of Oluhuta Village at AtinggolaSubdistrict in North Gorontalo District and to investigate the supporting and inhibiting factors of the village government efforts to encourage community participation in the development of Oluhuta Village at AtinggolaSubdistrict in North Gorontalo District. This study uses a qualitative method. The data collection employs observation, interviews, and documentation. The data analysis technique uses data collection, data reduction, data display, and conclusions. The results of this study indicate that the efforts of the village government to encourage community participation in village development are: 1) providing guidance to the community regarding environmental concern by keeping the environment clean from rubbish, 2) building community capacity in developing cattle production from the village government, and 3) fostering the decision-making process through village meetings. The supporting and inhibiting factors to the efforts of the village government to encourage community participation in village development, namely: 1) the supporting factors to the efforts of the village government to encourage community participation in village development are namely the openness and the commitment of the village government in involving the community in the development and the attitude of community cooperation in the development activities, and the level of relatively high community education, 2) the inhibiting factors to the efforts of the village government to encourage community participation in the development of the village come from the government itself, which is not capable of accounting for reporting the use of village finances so that village development financing is obstructed, and the ignorance attitude of the community in viewing the village development is not important, so in the implementation of development in Oluhuta Village most of the community does not participate in the development.